THE INFLUENCE OF WORKING CAPITAL, LIQUIDITY AND LEVERAGE ON PROFITABILITY IN THE FOOD AND BEVERAGE INDUSTRY ON THE IDX 2016-2021. - Risa Novia; Ristati; Rico Nur Ilham; Nurainun (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This study aims to determine the effect of Working Capital, Liquidity, and Leverage on Profitability in the Food and Beverage Industry on the Indonesia Stock Exchange. The data used in this study is secondary data from 18 manufacturing companies in the Food and Beverage sub-sector during the 2017 to 2021 research period, resulting in 108 observations. The method used to analyze the relationship between the independent variables and the dependent variable is the panel data regression method. The results show that partially, Working Capital has a positive and significant effect on the Profitability of Manufacturing Companies in the Food and Beverage sub-sector on the Indonesia Stock Exchange for the period 2016 to 2021. Liquidity has a negative and significant effect on the Profitability of Manufacturing Companies in the Food and Beverage sub-sector on the Indonesia Stock Exchange for the period 2016 to 2021. Leverage has a negative and significant effect on the Profitability of Manufacturing Companies in the Food and Beverage sub-sector on the Indonesia Stock Exchange for the period 2016 to 2021. Simultaneously, Working Capital, Liquidity, and Financial Performance have a positive and significant effect on the Profitability of Manufacturing Companies in the Food and Beverage sub-sector on the Indonesia Stock Exchange